Analysis of motor activity of professional football team players in the Ukrainian first league - Lebediev, S.; Beziazychnyi, B.; Bulgakov, O.; Stadnik, S.; Khudiakova, V.; Yefremenko, A.; Zhurid, S.; Petrusenko, N. (Journal of Physical Education and Sport, 2019)
Abstract. In this paper, the volume of high-speed motor activity of football team players in the Ukrainian First League is considered. Objective: The study was conducted among football team players in the Ukrainian First League in the 2017-2018 season. It was attended by 44 professional football team players in the Ukrainian First League. Results: The volume of motor activity of wing-backs provides for work in zones 1, 2, 4, 6, 7 and 9. Central defenders perform locomotor work mainly in zones 2 and 5. Central midfielders perform more diverse activities in 5 and 8 zones. The actions of the wing-backs provide for moving along the entire sideline in 1, 3, 4, 6 zones, as well as the wingers in 7, 9 and 10, 12 zones. Most of the time, the attack line players are in zones 8 and 11. Thus, the central defenders and wing-backs are inherent in work, which is performed mainly in the aerobic mode, the central midfielders, wingers and forwards are characterized by the performance of motor actions in the aerobic-anaerobic mode, and for the players of the line of attack compared to other roles - in the anaerobic mode. Conclusions. It was established that the motor actions of the central defenders per game are 8015 m (6381 m - at a slow pace, 1232 m - an average of 406 m - high), wing-backs are 9252 m (6651 m; 1712 m; 889 m, respectively), central midfielders 11261 m (7897 m; 3215 m; 1149, respectively), wingers - 10786 m (7141 m; 2575 m; 1070 m, respectively), forwards - 9799 m (5013 m; 2118 m; 2668, respectively).